2015
DOI: 10.1111/hel.12190
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori Infection is Positively Associated with Metabolic Syndrome in Taiwanese Adults: a Cross‐Sectional Study

Abstract: H. pylori infection is positively associated with metabolic syndrome, especially in females. The causal relationship between H. pylori infection and metabolic syndrome warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
66
7
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 45 publications
6
66
7
2
Order By: Relevance
“…Previous studies regarding the association of H. pylori infection with lipid metabolism showed relatively consistent evidence, but conflicting results also exist57182930. Especially, low socioeconomic level and crowded living conditions are important risk factors in H. pylori infection1516.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies regarding the association of H. pylori infection with lipid metabolism showed relatively consistent evidence, but conflicting results also exist57182930. Especially, low socioeconomic level and crowded living conditions are important risk factors in H. pylori infection1516.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are several studies regarding the role of H. pylori in risk factors of cardiovascular disease including type 2 diabetes, hypertension, dyslipidemia, obesity or metabolic syndrome57181920. However, only a few studies have investigated the relationships of H. pylori infection with each risk factor of cardiovascular disease.…”
mentioning
confidence: 99%
“…Accumulated evidence has suggested that this infection is associated with metabolic diseases, such as metabolic syndrome (Chen et al, 2015a, Chen et al, 2015b), type 2 diabetes mellitus (T2DM) (He et al, 2014b) and atherosclerotic diseases (He et al, 2014a), yet the underlying mechanism is obscure. Insulin resistance (IR) and subsequent hyperinsulinemia are the key pathogenic factors contributing to these metabolic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, a cross-sectional study of a large population of Japanese adults evaluated the concentration of HP-specific immunoglobulin G (IgG) and found that HP-infected subjects had a significantly higher risk of MetS [10]. Another study reported a similar relationship [11], while others did not [12, 13]. These discrepancies may be related to the variation in HP-infection and gastritis status in the study populations.…”
Section: Introductionmentioning
confidence: 99%